2022
DOI: 10.1002/anie.202210765
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and Spontaneous Oxidation and Reduction in Microdroplets by the Water Radical Cation/Anion Pair

Abstract: Microdroplets show unique chemistry, especially in their intrinsic redox properties, and to this we here add a case of simultaneous and spontaneous oxidation and reduction. We report the concurrent conversions of several phosphonates to phosphonic acids by reduction (RÀ P ! HÀ P) and to pentavalent phosphoric acids by oxidation. The experimental results suggest that the active reagent is the water radical cation/anion pair. The water radical cation is observed directly as the ionized water dimer while the wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
103
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(107 citation statements)
references
References 53 publications
4
103
0
Order By: Relevance
“…In view of the above advances, the spontaneous and strong reducing power of water microdroplets should be able to reduce and fixate CO 2 . Previous studies showed that water microdroplets could convert CO 2 into formate with or without the addition of triazole as a catalyst. , In this study, we take advantage of the reducing power of water microdroplets to generate an exotic radical anion of iodopentafluorobenzene (C 6 F 5 I •– ) by simply spraying the water solution of C 6 F 5 I into microdroplets in a N 2 -filled glovebox. To reveal the electronic nature of this anion, a combination of gas-phase anion photoelectron spectroscopy (PES) and theoretical calculation shows that the excess electron of C 6 F 5 I •– is located on the σ* antibonding orbital of the C–I bond, unlike most radical anions with benzene rings whose excess electrons prefer to be on the π* antibonding orbital.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above advances, the spontaneous and strong reducing power of water microdroplets should be able to reduce and fixate CO 2 . Previous studies showed that water microdroplets could convert CO 2 into formate with or without the addition of triazole as a catalyst. , In this study, we take advantage of the reducing power of water microdroplets to generate an exotic radical anion of iodopentafluorobenzene (C 6 F 5 I •– ) by simply spraying the water solution of C 6 F 5 I into microdroplets in a N 2 -filled glovebox. To reveal the electronic nature of this anion, a combination of gas-phase anion photoelectron spectroscopy (PES) and theoretical calculation shows that the excess electron of C 6 F 5 I •– is located on the σ* antibonding orbital of the C–I bond, unlike most radical anions with benzene rings whose excess electrons prefer to be on the π* antibonding orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Researches from our group and others have shown that water microdroplets exhibit unusual reaction properties that are not observed in bulk water or other organic solvents. One possible reason for the unique properties of water microdroplets is the large amount of hydroxyl radicals at the water–gas interface produced by a strong electric field and by contact electrification . Taking advantage of this feature, our group and others have shown that hydrogen peroxide forms in water microdroplets. The hydrogen peroxide originates from the recombination of two hydroxyl radicals at the surface of the water microdroplet.…”
mentioning
confidence: 91%
“…The evaporation of aniline from microdroplets may account, part, for the poor yield. 15 N-ammonium hydroxide solution ( 15 NH 4 OH) is used to trace the origin of N atoms in the aniline product. Similar with the experiments showed above, benzoic acid is dissolved in 15 NH 4 OH (28% water solution).…”
mentioning
confidence: 99%
“…[17][18][19] Moreover, the interfacial effects cause spontaneous oxidation and reduction in aqueous microdroplets without adding reducing or oxidizing agents. 17,20,21 Reactive species attributed to spontaneous redox are still under debate, while data from different experiments suggest hydroxy radicals, hydrogen peroxide, water radical cations, and electrons formed at the microdroplet air-water interfaces are highly reactive oxidizing and reducing agents. 20,21 Microdroplets for reaction acceleration are often generated by electrospray, where sufficiently strong electric force is applied to the solution of a reaction mixture.…”
Section: Introductionmentioning
confidence: 99%